Dialektika Relasi Gender dan Kekerasan Budaya dalam Komunikasi Keluarga untuk Pencegahan Stunting - Meryana Micselen Doko; Fadil Mas'ud; Daud Yefkanius Nassa; Petrus Ana Andung (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study aims to examine the dialectics of gender relations and cultural violence manifested within family communication regarding stunting mitigation in Sillu Village, Kupang Regency. Utilizing a qualitative case study approach, data were gathered through in-depth interviews with community leaders, medical professionals, and married couples with stunted children. The findings reveal that stunting mitigation is significantly hindered by a dominant patriarchal hegemony that restricts women’s bargaining power in health-related decision-making. Domestic communication dialectics are characterized by a conflict between modern health education and culturally violent constructs, such as dietary taboos for pregnant women and customary postpartum restrictions that obstruct infant access to healthcare facilities. This phenomenon further exacerbates the prevalence of stunting. Moreover, nutrition literacy is predominantly targeted at mothers, whereas financial control remains vested in fathers, who tend to be passive in domestic affairs. Consequently, this study recommends the implementation of gender-responsive health communication strategies within the family. This involves actively engaging fathers as health communicators and initiating community-based advocacy with traditional leaders to deconstruct cultural myths and customary norms that impede optimal maternal and child nutrition.